A multi-sensory tutoring program for students at-risk of reading difficulties: Evidence from a randomized field experiment - Martin Bøg; Jens Dietrichson; Anna Aldenius (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
Although reading is a fundamental skill, many students leave school without being proficient readers. We examine a literacy program targeting students most at-risk of reading difficulties in kindergarten and first grade. The program includes multi-sensory learning methods, which focus on phonological awareness and phonics and are delivered in a one-to-one or one-to-two tutoring setting. Using a randomized field experiment with 161 students in 12 Swedish schools, we find large positive effects on our two primary outcomes measures: a standardized test of decoding and a standardized test of letter knowledge. We also find positive effects on measures of phonological awareness and self-efficacy and small and statistically insignificant effects on measures of enjoyment and motivation. The program compares favorably to similar programs in terms of cost-effectiveness.
Keywords: I00; I20; I24; I3; J24; Z18; 330; phonological awareness; phonics; tutoring; multi-sensory; kindergarten; first grade; Sweden